Context of water transport related drownings in Bangladesh: a qualitative study - Jagnoor Jagnoor; Caroline Lukaszyk; Kamran ul Baset; Rebecca Ivers; Shamima Easmin; Aminur Rahman (BMC, 2019)
Abstract Background Bangladesh has one of the highest drowning mortality rates in the world. The use of unregulated water transportation may contribute to this burden, with 38% of all passenger traffic occurring by water. The present study aims to identify provider and end user perception on water transport related drowning risk, and barriers and facilitators for improving water safety practices. Methods A qualitative study was conducted in a riverine area of Bangladesh, the Barishal division. Data was collected through 18 in-depth interviews, two small group discussions and six observations in February-March 2016. Content analysis was conducted, guided by domains of Haddon's matrix for injury prevention. Results A range of unsafe behaviours, practices and conditions were identified at pre event, event and post event stages of water transport related drownings. It was also recognised it is not only the regulation of water transport but other factors such as occupational insecurities, poor access to rescue services and healthcare, migration and capacity for skill development among providers that contribute to unsafe water transport practices and drowning risk. Conclusion There are some immediate measures that can be implemented, with some monitoring and accountability processes for water transport safety. However, there is need for robust data to quantify transport related drowning, making a case for prioritization and action by relevant stakeholder such as government and transport providers.